Yerevan Brickwork Residential Building Architecture and the Importance of Geographic Information Systems (GIS) in Preservation of Architectural Monuments and Structures - Evlin Ordoukhanian; Shahen Shahinyan (Journal of Architectural and Engineering Research)
Many buildings were built in Yerevan with bricks. The specifics of brickwork, residential buildings, architecture, and building art in Yerevan have become the subject of the article. Especially, the characteristics of Iranian architecture are observed in the architecture of residential houses in Yerevan. The building material is mainly brick, and the front decoration of the buildings is carried out through the decorative brick masonry, which is more typical of Iranian architecture, with unique solutions of the decoration elements and wooden balconies. This combination points to the skill of Armenian architects and masters. This research aims to gather and maintain accurate information about brick structures, which significantly impacts their preservation. In a GIS environment, it is possible to combine vector and text information. The recommended technology makes it possible to see the location of the object on the map, not only in two dimensions but also in a 3D model. The proposed data processing in the GIS environment, both graphic (vector) data processing and linking of textual data to them, is already carried out. As a result, a complete database is obtained, which can be published for free use as well as serve as a basis for the preparation of maintenance or restoration projects, further monitoring, and analysis.